The Effectiveness of Kinesio Taping in Recovering From Delayed Onset Muscle Soreness: A Crossover Study - Kirmizigil, Berkiye; Chauchat, Jeffry Roy; Yalciner, Omer; Iyigun, Gozde; Angin, Ender; Baltaci, Gul (Human Kinetics Publ Inc, 2020)
Context: Kinesio taping (KT) is a popular taping technique used in the recovery process; however, in the relevant literature, there is no real consensus on its efficacy. Objective: To investigate whether rectus femoris KT application after delayed onset muscle soreness enhances recovery of muscle soreness, edema, and physical performance. Participants: A total of 22 healthy amateur male athletes participated in this study. Design: Randomized, crossover study. Setting: Human performance laboratory of the university. Interventions: Participants performed an exercise protocol inducing delayed onset muscle soreness. They accomplished 2 distinct trials, with or without KT. The washout period between trials was 6 weeks. For the KT condition, KT inhibition technique was used and applied immediately after exercise bilaterally on rectus femoris. Main Outcome Measures: Range of motion, muscle soreness, and edema were measured at baseline, 30 minutes, 24, 48, and 72 hours postexercise. Dynamic balance, sprint, and horizontal jump were evaluated at similar time frame except for 30-minute postexercise. Results: The findings showed that there were no significant differences between the KT group (KTG) and control group for all outcome variables (P> .05). Muscle soreness returned to baseline values 72 hours postexercise only within the KTG (P> .05). Although the horizontal jump performance decreased substantially from baseline to 24 and 48 hours postexercise only within the control group (P < .05), the performance increased significantly from 24 to 72 hours postexercise within the KTG (P < .05). Balance increased significantly from baseline to 48 hours postexercise (P < .05) in both groups. Balance also increased significantly from baseline to 72 hours postexercise only within the KTG (P < .05). The effect size of soreness which is our primary outcome was large in both groups (r> .5). Conclusions: KT is favorable in the recovery of muscle soreness after delayed onset muscle soreness. KT has beneficial effects on horizontal jump performance and dynamic balance.
Keywords: recovery; pain; edema; physical performance; Kinesio tape